Bangladesh development effectiveness brief. (Metro Manila, Philippines Asian Development Bank, 2017)
Bangladesh still faces challenges in creating enough productive jobs to reduce poverty and unlock the country development potential. Under the Country Partnership Strategy (CPS) 2016 2020, ADB will finance priority investments in energy, transport, and urban infrastructure and in human capital development to diversify the economy and release long term growth potential. Such support will also help make growth more inclusive by accelerating rural and regional development. The CPS 2016 2020 will also help speed up private sector development, develop capacity and improve governance, deepen regional cooperation and integration, and promote gender equality for inclusive growth.
Keywords: Public administration -- Bangladesh; Sustainable development; Electronic books